2015
DOI: 10.1590/s1519-99402015000100005
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization losses in Tanzania grass fertilized with urea

Abstract: Palavras-chave:Panicum maximum, fertilizante nitrogenado, pastagem Rev. Bras. Saúde Prod. Anim., Salvador, v.16, n.1, p.253-264 jan./mar., 2015 http://www.rbspa.ufba.br ISSN 1519 9940 http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Regardless of the formulation, the highest volatilization rates were observed near the 3rd day after application. Some studies also observed a high nitrogen volatilization in the early days after urea application in soil (Raymond et al, 2016;Rech et al, 2017;Soares Filho et al, 2015). The reason for this phenomenon is the rapid urea hydrolysis, which depends on the physical and chemical properties of the soil, as well as the amount of fertilizer applied in excess of that utilized by plants (Sigurdarson et al, 2018;Vahed et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the formulation, the highest volatilization rates were observed near the 3rd day after application. Some studies also observed a high nitrogen volatilization in the early days after urea application in soil (Raymond et al, 2016;Rech et al, 2017;Soares Filho et al, 2015). The reason for this phenomenon is the rapid urea hydrolysis, which depends on the physical and chemical properties of the soil, as well as the amount of fertilizer applied in excess of that utilized by plants (Sigurdarson et al, 2018;Vahed et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…No entanto dose de 50 kg ha -1 de N apresentou menor quantidade de N-NH 3 volatilizado quando comparada às maiores doses (Figura 7). Resultados também observados por Soares Filho et al (2015), as perdas de NH3 foram superiores para 100 e 150 kg ha -1 N do que para 50 kg ha -1 no outono e no verão, as porcentagens de perdas de N nos três dias após a aplicação levou à maior perda agregada.…”
Section: Maranduunclassified
“…Isto faz com que a camada limítrofe em torno do grânulo do fertilizante se alcalinize, volatilizando a amônia gerada em meio básico. A quantidade de N perdida por volatilização após a aplicação de ureia sobre a superfície do solo pode atingir valores extremos, próximos a 80% do N aplicado (BERNARDI et al 2010), sendo mais comum valores entre 16 e 40% (WERNECK et al 2012, SOARES FILHO et al 2015. A eficiência da ureia é aumentada se ocorrer chuva de 5 mm ou mais, até dois dias após a sua aplicação (WHITEHEAD 1995).…”
Section: Abstract: Acidity Indicators Natural Pasture Limingunclassified